A Convergence of Filipino Worlds: An Onomastic Reading of Edgar Calabia Samar’s Janus Silang Novels - G. Ancheta, Maria Rhodora (SARE: Southeast Asian Review of English, 2021)
Edgar Calabia Samar’s Janus Silang book series is a significant body of contemporary young adult fantasy novels in the Philippines. Samar’s ambitious series that successfully melds alternate online tech-worlds, everyday Filipino life, and ancient supernatural, god-inhabited worlds, is worthy of study. In creating this fantasy world, the Janus Silang series underscores the richness of Filipino mythology and lore by cohesively layering these lived worlds by way of spatial and temporal play. This paper wishes to study the value of this “world(s)-building”, entering this by way of the study of onomastics, the study of proper names of all kinds and the origins of names. Using both toponomastics and anthroponomastics, or the study of place names and human naming, respectively, this inventive, powerful focus on naming solidifies the Janus Silang series’ development of unique Filipino characters and narratives and its reintroduction of the cultures of its imaginary worlds for young, contemporary Filipino and global readers